Sodium nitroprusside improves circulatory failure in rabbit acute pulmonary embolism combined with shock model possibly by enhancing NO release and inhibiting TLR4/NF-кB/HIF-1α signaling pathway - Zhou, Yuchan; Wang, Yuting; Yu, Delong; Liu, Xiaoyan; Cao, Wenjuan; Li, Huanhuan; Gu, Ye; Hu, Liqun; Bai, Yupeng (Frontiers in Physiology, 2025)
Sodium nitroprusside (SNP) is a fast-acting non-endothelium-dependent vasodilator, which is commonly used to treat diseases such as hypertensive emergencies and acute heart failure. However, there are few experimental studies evaluating the effects and mechanism of SNP on acute pulmonary embolism. To explore the mechanism of action of SNP in acute pulmonary embolism combined with shock, we randomly divided rabbits into sham operation group (S group, n = 8), model group (M group, n = 8), and SNP group (SNP group, n = 8). The rabbit model of acute massive pulmonary embolism with circulatory shock was established by injecting autologous blood clots into the pulmonary artery. Pulmonary angiography showed that the mean pulmonary artery pressure increased significantly and the mean arterial pressure decreased significantly in the model group, which could be reversed by SNP treatment. In addition, the TLR4/NF-κB/HIF-1α pathway signaling pathway was activated in the embolic and non-embolic areas of the lung tissue in the M group, promoting the release of inflammatory factors such as IL-6 and TNF-α, downregulation of endogenous NO expression in the model group. After SNP treatment, the expression of TLR4/NF-κB/HIF-1α pathway signals in the embolic and non-embolic areas was downregulated, the release of inflammatory factors was reduced, the release of vascular NO was increased. Our study shows that SNP has a protective effect on acute pulmonary embolism combined with shock. Its protective effect may be related to inhibiting the TLR4/NF-κB/HIF-1α signaling pathway and increasing NO release in the embolic and non-embolic areas, thereby dilating pulmonary blood vessels, reducing the release of inflammatory factors and partially reversing circulatory failure in this model.